2020
DOI: 10.3389/fendo.2020.610519
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics, Diagnostic Delays, Treatment Patterns, Treatment Outcomes, Comorbidities, and Treatment Costs of Acromegaly in China: A Nationwide Study

Abstract: PurposeAcromegaly is a rare, intractable endocrine disease. We aimed to describe the patient characteristics, diagnostic delays, treatment patterns, treatment outcomes, comorbidities and treatment costs of acromegaly in China.MethodsThis is a nationwide cross-sectional study. Patients diagnosed with and treated for acromegaly between 1996 and 2019 across China were surveyed via the Chinese Association of Patients with Acromegaly platform.ResultsIn total, 473 patients (58.8% females, mean age at diagnosis: 39.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 58 publications
2
18
1
4
Order By: Relevance
“…On the other hand, some studies confirm an improvement in clinical complaints and HrQoL after biochemical control. For example, in 2020, a Chinese study concluded that there is improvement in patients’ symptoms and HrQoL after patients' control [ 21 ]. However, despite the statistically significant reduction in their symptom frequency after biochemical control, the persistence of these symptoms was demonstrated in a significant proportion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies confirm an improvement in clinical complaints and HrQoL after biochemical control. For example, in 2020, a Chinese study concluded that there is improvement in patients’ symptoms and HrQoL after patients' control [ 21 ]. However, despite the statistically significant reduction in their symptom frequency after biochemical control, the persistence of these symptoms was demonstrated in a significant proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly prevalence ranges from 20 to 130 people per million inhabitants [2,4,[7][8][9][10][11][12][13][14][15], with an annual incidence of 2 to 11 cases per million people [4,[7][8][9][10]13,15]. Most studies show that there are no sex differences in acromegaly prevalence [2,4,6,16]; however, some studies have shown a slightly higher prevalence among women [12].…”
Section: Acromegalymentioning
confidence: 99%
“…Acromegaly is a rare chronic disease caused by an excessive secretion of growth hormone (GH), mostly due to an adenoma of the anterior pituitary gland and resulting in an increased circulating concentration of insulin-like growth factor 1 (IGF-1), the main effector of GH activity. It is characterized by a slow progression of signs and symptoms and multisystemic involvement, leading to physical alterations, progressive somatic changes, and a complex range of systemic comorbidities [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Броят на публикуваните проучвания е ограничен, като от всички идентифицирани 176 проучвания само 16 отговарят на изследователския въпрос. Повечето публикувани проучва-ния са проведени в САЩ (n=6) [20,23,24,26,29,32], следвани от Канада (n=2) [17,21], Швеция (n=2) [25,28], Китай (n=1) [31], Испания (n=1) [22], Италия (n=1) [18], Полша (n=1) [27]. Две от идентифицираните проучвания представляват систематичен преглед [19,30].…”
Section: характеристики на проучванията обобщение и обсъждане на получените резултатиunclassified